THE IMPORTANCE OF AXIOLOGICAL APPROACH IN PREPARING STUDENTS FOR FAMILY LIFE (American Journal of Interdisciplinary Research and Development, 2026)
The article talks about the use of psychological and pedagogical technologies that allow students to form comprehensive knowledge about the family based on the axiological approach, and because of this, the possibility of acquiring knowledge and skills about the family. It is scientifically based that it allows the student to succeed in life and be socially active in society.